ԶԻՆՎՈՐՆԵՐԻ ՀՈԳԵԲԱՆԱԿԱՆ ՀԱՐՄԱՐՈՒՄԸ ԶԻՆՎՈՐԱԿԱՆ ԾԱՌԱՅՈՒԹՅԱՆԸ - Bdoyan, L. N. (Արդի հոգեբանություն, 2019)
The article discusses the adaptation issues and the adaptability of soldiers to military service. The results of the study of the socio-psychological adaptation of military personnel are analyzed. The study showed that military personnel while serving in the army do not avoid problems, have internal control, sympathize with other people, are adaptive, which can contribute to increasing the efficiency of military service.